2017
DOI: 10.3389/fnins.2017.00644
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Attenuates Visceral Hypersensitivity by Inhibiting JAK2/STAT3 Signaling Pathway in the Descending Pain Modulation System

Abstract: Electroacupuncture (EA) has been used for treating visceral hypersensitivity (VH). However, the underlying molecular mechanism remains unclear. This study was aim to testify the effect of EA on ileitis-provoked VH, and to confirm whether EA attenuates VH through Janus kinase 2 (JAK2)/signal transducers and activators of transcription 3 (STAT3) signaling pathway in the periaqueductal gray (PAG)-the rostral ventromedial medulla (RVM)-the spinal cord dorsal horn (SCDH) axis. Methods:Goats were anesthetized and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 79 publications
(92 reference statements)
0
50
0
Order By: Relevance
“…A recent systematic review and meta-analysis of randomized controlled trials (RCT) of clinical acupuncture for IBS confirmed the effectiveness of traditional Chinese medicine acupuncture for IBS [2][3][4][5]. Electroacupuncture (EA) can inhibit visceral injury responses at multiple levels [6,7]. EA at body surface acupoints can inhibit visceral injury response at multiple nerve levels with the largest inhibitory effect on spinal dorsal horn [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of randomized controlled trials (RCT) of clinical acupuncture for IBS confirmed the effectiveness of traditional Chinese medicine acupuncture for IBS [2][3][4][5]. Electroacupuncture (EA) can inhibit visceral injury responses at multiple levels [6,7]. EA at body surface acupoints can inhibit visceral injury response at multiple nerve levels with the largest inhibitory effect on spinal dorsal horn [8].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, CD pediatric patients coexisting functional GI disorders showed rectal hypersensitivity 2 . Our earlier studies 32,40,42 also reported VH in response to graded CRD in rats and goats with TNBS-induced ileitis. Researches demonstrate that VH across the organs is due to the central sensitization of spinal cord neurons receiving convergent input from different organs 69,70 or descending bulbospinal inhibition of sacral dorsal horn neurons in response to chronic intestinal tissue irritation 71 .…”
Section: Discussionmentioning
confidence: 71%
“…Recently, MPO activity has been assayed as a biochemical indicator of inflammation. It is observed in the neutrophils and their oxidative products, particularly involved in the tissue damage process during the acute stage of 32 reported that the MPO concentration in TNBS-injected ileum of the goats was increased on day 7 rather than on day 22. Increasing sets of evidence show the importance of PAR-2 both in gastroenteritis 11,45,46 and inflammatory condition of the central nerve system 17,47,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analgesic effect of EA application in VH has been extensively reported [ 27 29 ], and therefore the molecular mechanisms involved in this effect are attracting more attention. Previous studies have indicated that the endogenous opioid pathway in the periphery [ 27 , 28 ], the JAK2/STAT3 signaling pathway in the PAG-RVM-SCDH axis [ 29 ], the corticotropin-releasing hormone in the colon, spinal cord, and hypothalamus [ 15 ], and other pathways are all involved in mediating the effects of EA on VH. In agreement with previous research by our group [ 30 ], several studies indicate that EA attenuates VH via reduction of both colonic enterochromaffin cell number and 5-HT concentration in the brain-gut axis [ 29 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%